The Application of Fiqhiyah Principles in the Settlement of Inheritance Disputes in Indonesia from the Perspective of Islamic Law and National Law - Dwi Dasa Suryantoro (Institut Agama Islam Nahdlatul Ulama Tuban, 2025)
Settlement of inheritance disputes in Indonesia is a complex issue because it involves aspects of Islamic law, national law, and diverse customs. The rules of fiqhiyyah in Islamic law actually provide clear guidelines in the distribution of inheritance based on the Qur'an and Hadith, but in practice they often experience challenges due to differences in interpretation and local cultural influences. This study uses a normative approach by analyzing laws and regulations, Compilation of Islamic Law (KHI), and religious court decisions to examine the implementation of fiqhiyyah rules in resolving inheritance disputes. The results of the study show that although KHI has accommodated the principles of Islamic inheritance law, its implementation in the field is not always consistent with the provisions of fiqh due to the influence of customary and low public understanding of inheritance rights. In addition, differences between generations in the view of the fairness of inheritance distribution also affect the dynamics of disputes. Therefore, strategic steps are needed such as legal education, strengthening the role of religious courts, and implementing mediation involving parties who understand Islamic law and positive law. Efforts to harmonize the applicable legal system are important to realize a fair, proportionate settlement of inheritance disputes in accordance with the values of justice in society.